2021
DOI: 10.3390/ijerph182010664
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Study on Ecological and Economic Coupling of the Yellow River Basin

Abstract: The coupling and coordination relationship between ecology and the economy in the Yellow River Basin is a hot topic in sustainable development research. Said research has important guiding significance for the ecological security and comprehensive development of the Yellow River Basin. Taking the Yellow River Basin as the object of our study, based on the data of the economy, energy consumption data, ecology data and water resources data, we construct an indicator system of the economic development and ecologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…The ecological environment coordinated development index shows a trend of a wave-like rise [ 49 ], which can be attributed to the promotion of environmental protection awareness among people, the improvement of the environmental protection system, and the construction of large-scale basic environmental protection facilities. Taking 2012 as a key turning point, the ecological environment development index before 2012 was on a declining curve, which proves the rapid economic development in the basin led to the deterioration of the ecological environment [ 48 , 50 ]. While after 2012, the governance of ecological environmental protection, coordinated economic development, and the transformation and upgrading of heavily polluting enterprises were enhanced under the guidance of the “Twelfth Five-Year Plan” and the “Thirteenth Five-Year Plan”, as a result, the ecological environment system and economic development system appear with an upward trend again.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The ecological environment coordinated development index shows a trend of a wave-like rise [ 49 ], which can be attributed to the promotion of environmental protection awareness among people, the improvement of the environmental protection system, and the construction of large-scale basic environmental protection facilities. Taking 2012 as a key turning point, the ecological environment development index before 2012 was on a declining curve, which proves the rapid economic development in the basin led to the deterioration of the ecological environment [ 48 , 50 ]. While after 2012, the governance of ecological environmental protection, coordinated economic development, and the transformation and upgrading of heavily polluting enterprises were enhanced under the guidance of the “Twelfth Five-Year Plan” and the “Thirteenth Five-Year Plan”, as a result, the ecological environment system and economic development system appear with an upward trend again.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…According to existing theoretical results [ 44 ], we construct the index system from three subsystems of ecological environment, economic development, and public health system to measure the coordinated development level of the Yellow River Basin. The existing research results, which have established two index systems of economic development and ecological development, are limited [ 48 ]. First, the original index system only considered the two dimensions of economic structure and resource consumption when measuring economic development.…”
Section: System Construction and Data Sourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that there is a disconnection between the economic subsystem and the resource-environment subsystem. In a case study of the Yellow River Basin, Zhao et al [ 11 ] found that ecological construction is important to eliminate the contradiction between environment and economy. In the coupling coordinated development research of 31 provincial capital cities in China, Fan et al [ 12 ] discovered that the coordination development of economy and environment is vital to sustainable development.…”
Section: Literature Reviewmentioning
confidence: 99%